PERAN INHIBITOR KOROSI PADA PROSES DAN HASIL PRODUKSI BAJA: STUDI LITERATUR REVIEW - sahril - sabirin; andika cahya febiawan; Ardika Achmad Gustama; Faris Ahmad Irfany; Yudi Oktavia Ramadhan; Ananda Yhuto Wibisono Putra (Jurnal Teknik Mesin dan Mekatronika (Journal of Mechanical Engineering and Mechatronics), 2023)
This study aims to determine the definition of corrosion, types of corrosion, corrosion protection in the steel production process, corrosion protection using inhibitors, types of inhibitors, and types of inhibitors for various materials. The research approach is a qualitative approach with a literature review research method. The research data obtained were analyzed descriptively and quantitatively. This research was conducted by systematically analyzing literary sources in the form of scientific articles, books, accompaniments and theses from reliable sources. The results of this study examine the process of corrosion protection in steel production processes and products using various types of inhibitors. The result is that the coiled coil material is subjected to a continuous curing line to produce galvanized steel coils, which can lead to corrosion of the material, among other things by environmental concentrations. The corrosion process can be prevented in various ways, one of which is with an inhibitor. The types of inhibitors used consist of organic and inorganic materials. The inorganic inhibitors used were EonCor W203, while the organic inhibitors used were extracts of guava leaves, tea leaves, soybeans and coffee.